Dialogue as a trans-disciplinary concept: Martin Buber’s philosophy of dialogue and its contemporary reception - Mendes Flor, Paul (Studia Judaica, 2015)
"This volume of essays takes as its point of departure Martin Buber's principle of dialogue, which he applied as a comprehensive hermeneutic method for the study of various cultural phenomena. The volume critically evaluates the methodological purchase to be gained by the introduction of Buber's conception of dialogue in political theory, psychology and psychiatry, and religious studies"--